An Overview of Increasing Incidents of Bottlenose Dolphin Harassment in the Gulf of Mexico and Possible Solutions - Vail, Courtney S. (Frontiers in Marine Science, 2016)
The panhandle region of the Gulf of Mexico is known by scientists, regulatory agencies and conservation organizations as a ‘hotbed’ area of dolphin harassment. Interactions between humans and wild dolphins routinely occur through close vessel approaches or through direct contact associated with commercial or recreational fisheries, swim-with, or feeding activities. Such interactions are of serious concern for wild dolphin welfare and conservation under the U.S. Marine Mammal Protection Act, as well as for human safety. In recent years, an alarming number of dolphins in this region have been fatally wounded by gunshot, hunting arrows, or sharp tools (i.e., screwdriver). The potential to mitigate the detrimental impacts resulting from these human-dolphin encounters requires a comprehensive outreach strategy to address increasing incidents of harassment and vandalism, as well as an evaluation of the serious trends and challenges hampering dolphin protection in this region. In addition to the identification and conviction of perpetrators through the application of existing law, voluntary outreach programs offer real potential to educate and reform public attitudes and behaviors through community-based stewardship initiatives, which can foster dolphin protection in areas of high human-dolphin conflict. The development of these types of programs underlines the potential for non-regulatory approaches to serve as an effective means to reach and activate the public on some of the most pressing local and regional marine conservation issues. In tandem with regulations and enforcement, voluntary stewardship programs can provide stakeholders an opportunity to engage in local dolphin conservation efforts through a positive approach aimed to inspire